Design thinking: understand - improve - apply - and Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Springer, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phenomena. They continue with an exploration of tools which can help improve the adaptive expertise needed for design thinking. The final part of the book concerns design thinking in information technology and its relevance for business process modeling and agile software development, i.e. real world creation and deployment of products, services, and enterprise systems"–Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations